Natural groundwater eco-treatment (N-GET) for water supply at Johor, Malaysia - Musa, Sabariah; Hamdan, Rafidah; Radin Mohamed, Radin Maya Saphira; Denan, F. (Penerbit Akademia Baru, 2015)
Groundwater is an alternative source to supply water to consumers. The groundwater well is available at RECESS which is situated in UTHM campus containing low quality of groundwater. This research was conducted to identify the effectiveness of the Nature Groundwater Eco-Treatment (N-GET) system that has been designed at RECESS for daily usage. N-GET system is a natural treatment process without mixing any substances intended to improve the quality of groundwater can give benefits especially to users at RECESS. N-GET system uses four tanks in the treatment of groundwater which are aeration tanks, sedimentation tanks, suction tanks and distribution tanks. Seven parameters was tested which is pH, turbidity, dissolve oxygen (DO), manganese, sulphate, chloride and nitrate with 15 numbers of sample. The water quality (pH value, turbidity, dissolve oxygen (DO), manganese, sulphate, chloride and nitrate) was improved and this system 100% effectively to treat the contaminant of groundwater. After the treatment by using this system, the water was pass the water quality standard which produced by Ministry of Health Malaysia (KKM). Thus, this system was implemented that the usage of water from various sources with simple, easy, practical treatment and low cost of construction. Therefore, this system will trigger idea of producing groundwater treatment by applying the natural concept as well as for the best purpose and more environmental friendly in the future"